Mission-Based Monitoring, Evaluation and Learning (MEL) Platforms Asse ssment Report - Arntson, Laura; Giannoni, Tonya; Peek, Nancy; Saarlas, Kristin (USAID, 2017)
In 2016, the Bureau of Policy, Planning and Learning (PPL) commissione d an internal stocktaking of USAID's mission-based MEL (Monitoring, Ev aluation, and Learning) Platforms.